2016
DOI: 10.1051/0004-6361/201527129
|View full text |Cite
|
Sign up to set email alerts
|

The VIMOS Public Extragalactic Redshift Survey (VIPERS)

Abstract: We exploit the first public data release of VIPERS to investigate environmental effects in the evolution of galaxies between z ∼ 0.5 and 0.9. The large number of spectroscopic redshifts (more than 50 000) over an area of about 10 deg 2 provides a galaxy sample with high statistical power. The accurate redshift measurements (σ z = 0.00047(1 + z spec )) allow us to robustly isolate galaxies living in the lowest and highest density environments (δ < 0.7 and δ > 4, respectively) as defined in terms of spatial 3D d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
121
2

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

7
0

Authors

Journals

citations
Cited by 87 publications
(146 citation statements)
references
References 145 publications
19
121
2
Order By: Relevance
“…Our results are in very good agreement with other works performed with the VIPERS sample, that is, with the study of the galaxy stellar mass function per environment (Davidzon et al 2016, based on a previous VIPERS release) and the study of galaxy properties with relation to distance from filaments describing the VIPERS large-scale structure (Malavasi et al 2017, based on the same VIPERS release as this work, but with a different definition of environment). It is difficult to perform a quantitative comparison of our results with similar works in the literature because of the different environment definitions (or the same definition, but different tracer samples) and the different galaxy-type classification.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are in very good agreement with other works performed with the VIPERS sample, that is, with the study of the galaxy stellar mass function per environment (Davidzon et al 2016, based on a previous VIPERS release) and the study of galaxy properties with relation to distance from filaments describing the VIPERS large-scale structure (Malavasi et al 2017, based on the same VIPERS release as this work, but with a different definition of environment). It is difficult to perform a quantitative comparison of our results with similar works in the literature because of the different environment definitions (or the same definition, but different tracer samples) and the different galaxy-type classification.…”
Section: Discussionsupporting
confidence: 91%
“…We remark that this cosmology is outdated, with for instance σ 8 based on the first-year results of the Wilkinson Microwave Anisotropy Probe (WMAP1, Spergel et al 2003) being larger than more recent measurements such as WMAP7 (Komatsu et al 2011) and WMAP9 (Hinshaw et al 2013), where they find σ 8 to be of the order of 0.8. Davidzon et al (2016) showed that the density distribution is slightly different in two simulations based on the cosmologies from WMAP1 and WMAP3, but WMAP3 had a very low σ 8 (σ 8 = 0.7). Given that σ 8 (and also other cosmological parameters) from WMAP7 and WMAP9 is closer to that of WMAP1, we do not expect a large difference between simulations based on WMAP1 or WMAP7 and WMAP9, as also shown in Guo et al (2013).…”
Section: Mock Samplesmentioning
confidence: 95%
“…The photometric multi-wavelength coverage combines improved ugriz-bands photometry based on the T0007 release of the CFHTLS 1 and K s-band observations from the VIPERS Multi-Lambda Survey (VIPERS-MLS 2 , Moutard et al 2016a) or, when available, from the VISTA Deep Extragalactic Observations (VIDEO; Jarvis et al 2013) survey (more details in Davidzon et al 2013Davidzon et al , 2016Moutard et al 2016b). …”
Section: Physical and Structural Parameters Of Vipers Galaxiesmentioning
confidence: 99%
“…In contrast, when considering local density estimates, the GSMF seems to depend on environment, being steeper in less dense environments (e.g. Baldry et al 2006;Bolzonella et al 2010;Vulcani et al 2012;Davidzon et al 2016;Etherington et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Balogh et al 2001;Yang et al 2009;Calvi et al 2013;Vulcani et al 2011Vulcani et al , 2012Vulcani et al , 2013Vulcani et al , 2014bDavidzon et al 2016;Muzzin et al 2013;van der Burg et al 2015;Nantais et al 2016). Its shape has been described by a Schechter or a double Schechter function (Schechter 1976).…”
Section: Introductionmentioning
confidence: 99%